INSTYTUCJONALNO-PRAWNE PODSTAWY WSPÓŁPRACY SAMORZĄDU WOJEWÓDZTWA Z RZĄDEM W ZAKRESIE POLITYKI REGIONALNEJ - Kokocińska, Katarzyna (Wydział Prawa i Administracji UAM, 2008)
Regional policy is by law managed by the central government on the national level and by regional self-governments on the regional level. Collaboration between those organs requires a clearly defined system that will ensure legal grounds and institutions for adequate realisation o f the adopted regional policy. Those legal solutions must act as guarantees o f coherent activities carried out by public organs o f varied systems and competences as well as constitute safeguards of the sovereignty and independence o f self-governing local units. The analysis of the regulations presented in the paper leads to a conclusion that despite the seemingly important role that the legislator foresaw for regional self-governments, the state continues to exercise a key role in the regional policy those organs perform. This is mainly due to the fact that the responsibility for development at the national level vested to the Council o f Ministers also covers its activity in the regions. Neither the principles o f the development policy adopted in 2006, nor the Act on regional self-government offers a comprehensive mechanism that would ensure harmonious actions concerning regional policy decisions taken at the state and regional levels. Consequently, its realisation lacks coherence and fails to produce expected results.
INSTITUTIONAL AND LEGAL GROUNDS FOR COLLABORATION BETWEEN REGIONAL SELF-GOVERNMENTS AND THE GOVERNMENT IN THE SCOPE OF REGIONAL POLICY